The Involvement of Endogenous Enkephalins in Glucose Homeostasis - Vanessa Escolero; Laica Tolentino; Abdul Bari Muhammad; Abdul Hamid; Kabirullah Lutfy (Biomedicines, 2023)
Obesity has nearly tripled since 1975 and is predicted to continue to escalate. The surge in obesity is expected to increase the risk of diabetes type 2, hypertension, coronary artery disease, and stroke. Therefore, it is essential to better understand the mechanisms that regulate energy and glucose homeostasis. The opioid system is implicated in regulating both aspects (hedonic and homeostatic) of food intake. Specifically, in the present study, we investigated the role of endogenous enkephalins in changes in food intake and glucose homeostasis. We used preproenkephalin (ppENK) knockout mice and their wildtype littermates/controls to assess changes in body weight, food intake, and plasma glucose levels when mice were fed a high-fat diet for 16 weeks. Body weight and food intake were measured every week (n = 21–23 mice per genotype), and at the end of the 16-week exposure period, mice were tested using the oral glucose tolerance test (OGTT, n = 9 mice per genotype) and insulin tolerance test (n = 5 mice per genotype). Our results revealed no difference in body weight or food intake between mice of the two genotypes. However, HFD-exposed enkephalin-deficient mice demonstrated impaired OGTT associated with reduced insulin sensitivity compared to their wildtype controls. The impaired insulin sensitivity is possibly due to the development of peripheral insulin resistance. Our results reveal a potential role of enkephalins in the regulation of glucose homeostasis and in the pathophysiology of diabetes type 2.